Black girls must have it all : a novel - Allen, Jayne, 1978- (Allen, Jayne, 1978- Black girls must die exhausted series, 2023)
Tabitha Walker's carefully organized plan to achieve the life she wanted-- perfect job, dream husband, and stylish home-- has gone off the rails. Her checklist now consists of diapers changed (infinite), showers taken (zero), tears cried (buckets), and hours of sleep (what's that?). Tabby loves her new bundle of joy and motherhood, but then the news station announces that they will be hiring outside competitors for the new anchor position. And all of her relationships seem to be shifting out of their regular orbits. When Marc presents her with an ultimatum about their relationship, coupled with an extended "visit" from his mother, Tabby is forced to take stock of her life and make a new plan for the future. -- adapted from jacket